Nilai Kepemimpinan Tranformasional Efektif dalam Memperkuat Budaya Organisasi Sekolah - Taufikur Rohman Muzekki; Nur Hidayah Hurani; Muhammad Mukhlis Anshori (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
Abstract: Abstract This research aims to determine the value of effective leadership through the application of transformational leadership style on the organizational culture of schools. The research method used is a systematic literature review, exploring relevant literature. It was found that the transformational leadership style impacts the organizational culture of schools. This leadership style creates a school culture based on collaboration, support, and trust, and establishes a foundation of shared values and beliefs within the school.